Hubungan Antara Beban Kerja, Efikasi Diri, dan Stres Kerja pada Karyawan Unit Terminal Halim Perdanakusuma - Silva Cerliana Putri; Nur Makkie Perdana Kusuma (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
One of Halim Perdanakusuma Airport (HLP) units is the Terminal and Landside Service unit. Terminal Inspection Service (TIS) units in the unit and Customer Service (CS) have different job descriptions. However, at this HLP airport, some employees do work that is not part of their job description, namely TIS unit employees who do CS work, or vice versa. This condition indirectly impacts the workload and self-efficacy of employees in the TIS and CS units on work stress. This study aims to determine whether there is an influence between workload and work stress, the influence of self-efficacy on work stress, the influence of workload and self-efficacy simultaneously on work stress, and the coefficient of determination. This study uses a quantitative method with partial test hypothesis testing and simultaneous testing. Data was collected by distributing questionnaires containing 36 questions to 30 employees from the TIS and CS units. Before being distributed, the data had been validated and reliable. The data was then analyzed using the t-test (partial test), the f-test (simultaneous test), and the coefficient of determination. The study's results showed that (1) workload significantly affected work stress with a sig. Value of 0.000; (2) self-efficacy significantly affected work stress with a sig. Value of 0.000; (3) workload and self-efficacy simultaneously affected work stress with a sig. value of 0.000; and (4) the coefficient of determination obtained a result of 72.9%.